IMPLEMENTATION OF LOCAL WISDOM-BASED SCHOOL THROUGH DANCE EXTRACURRICULAR IN THE NGREKSO BUWONO DANCE - Umiatun, Hanik; Fajrie, Nur; Rondli, Wawan Shokib (JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
This research aimed to describe the application of local cultural wisdom in elementary schools through dance extracurricular activities in the Ngrekso Buwono dance. A qualitative approach was used in this research using ethnographic research. This research was conducted at SD Negeri I Blimbingrejo with the dance teachers. This research was obtained through observation, interviews, and documentation, which were then tested through triangulation sources. Data analysis was obtained using data reduction, data presentation, and conclusion. Based on the research results, the application of local wisdom at SD Negeri I Blimbingrejo in extracurricular activities (outside the learning hours). The extracurricular activity carried out is dance. Supporting factors that influence dance extracurricular activity are internal and external factors. Internal factors include the condition of students who have interests, talents, and motivation to take part in dance extracurricular activity. External factors include support from schools with dance teachers, adequate facilities and infrastructure, and support from parents.